Incidence of concurrent infection of Coli-Septicaemia and Infectious Bronchitis in an organised layer farm - YogeshPriya, S; Saravanan, M; RanjithKumar, M; KrishnaKumar, S (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
An outbreak of IB with colibacilosis and its diagnosis and management is reported. In an organised farm, the affected flock had a complaint of anorexia, dyspnoea, and weight loss and misshappened eggs. On examination of serum samples, IB showed HI titre of 64 with a GM value of 24.3 where as heart and liver swabs revealed the presence of E.coli organisms. ABST of the organism revealed sensitivity to Gentamicin, Cephalexin and intermediate sensititive to Enrofloxacin and Ciprofloxacin and resistant to Oxytetracycline. Based on the clinical signs, lesions and laboratory tests the outbreak was diagnosed as Infectious Bronchitis and Colisepticaemia and remaining flock was successfully managed with Gentamicin 4 mg/kg body weight twice daily at 24 hours interval along with supportive drugs. Biosecurity measures were advised to prevent subsequent infection.
Keywords: Infectious Bronchitis; Layers; Colisepticaemia; Antibiogram Studies